Impact of the Local Inflammatory Environment on Mucosal Vitamin D Metabolism and Signaling in Chronic Inflammatory Lung Diseases - Schrumpf, Jasmijn A.; van der Does, Anne M.; Hiemstra, Pieter S. (Frontiers in Immunology, 2020)
Vitamin D plays an active role in the modulation of innate and adaptive immune responses as well as in the protection against respiratory pathogens. Evidence for this immunomodulatory and protective role is derived from observational studies showing an association between vitamin D deficiency, chronic airway diseases and respiratory infections, and is supported by a range of experimental studies using cell culture and animal models. Furthermore, recent intervention studies have now shown that vitamin D supplementation reduces exacerbation rates in vitamin D-deficient patients with chronic obstructive pulmonary disease (COPD) or asthma and decreases the incidence of acute respiratory tract infections. The active vitamin D metabolite, 1,25-dihydroxy-vitamin D (1,25(OH)2D), is known to contribute to the integrity of the mucosal barrier, promote killing of pathogens (via the induction of antimicrobial peptides) and to modulate inflammation and immune responses. These mechanisms may partly explain its protective role against infections and exacerbations in COPD and asthma patients. The respiratory mucosa is an important site of local 1,25(OH)2D synthesis, degradation and signaling, a process that can be affected by exposure to inflammatory mediators. As a consequence, mucosal inflammation and other disease-associated factors, as observed in e.g. COPD and asthma, may modulate the protective actions of 1,25(OH)2D . Here, we discuss the potential consequences of various disease-associated processes such as inflammation and exposure to pathogens and inhaled toxicants on vitamin D metabolism and local responses to 1,25(OH)2D in both immune- and epithelial cells. We furthermore discuss potential consequences of disturbed local levels of 25(OH)D and 1,25(OH)2D for chronic lung diseases. Additional insight into the relationship between disease-associated mechanisms and local effects of 1,25(OH)2D is expected to contribute to the design of future strategies aimed at improving local levels of 1,25(OH)2D and signaling in chronic inflammatory lung diseases.